Management of Model Development for Facilitation of Real Work Facilitation Teachers for PJOK & BK - Lidya Ardiyan; Moh. Joharis Lubis (Budapest International Research and Critics University, 2022)
The driving teacher as an agent of change and transformation of education in his community. Management, The development of the Facilitation Model for Real Work (FKN) for PJOK and BK teachers is carried out to encourage driving teachers to continue to move after completing the Motivating Teacher Education program. Through this FKN Program, it is hoped that the driving teachers will become more skilled as coaches in teacher training in their practice communities. With the FKN Research and Development model, it is managed by the PPPPK Penjas & BK as the Satker managing the Program, consisting of 10 teachers of the FKN guide and content development team, six expert validators as reviewers, to proceed to the implementation of a limited trial in the form of the FKN Coaching Clinic with 117 teachers. They are driving Force-1 PJOK and BK, followed by a Focus Group Discussion with participants and validators to review the readiness of the FKN model before it is implemented. FKN is carried out in 3 regions in 22 provinces spread throughout Indonesia in the implementation stage. Attitude Evaluation Participants averaged 89 points in the very good category. Evaluation of Skills Participants averaged 92 points in the very good category. Knowledge evaluation through posttest with an average score of 67 with good category. The final score is the accumulation of evaluation values of attitudes, skills, and knowledge with a proportion of 80% (40% attitude value + 60% skill value) + 20% posttest value. The average final score is 92, with a very good category. The success of this FKN has become one of the alternatives that other stakes can also implement in making post-program activities for motivating teachers to keep encouraging teachers to do work for the surrounding community.